Plantas de mangue Laguncularia racemosa (L.) C.F.Gaertn.,Avicennia germinans Stapf & Leechman e Rhizophora mangle L. como bioindicadoras de contaminação por poluentes: caracterizações ecofisiológicas e ecotoxicológicas em manguezais da área portuária do Itaqui, Maranhão - CASTRO, Ana Maisy de Miranda (2024)
Mangrove plants have developed efficient antioxidant systems to protect themselves from stress caused by the most diverse pollutants. Studies like this can provide an understanding of some adaptive processes of mangrove plants in the face of pollution, responsible for giving mangroves the ability to survive in polluted areas. The research evaluated environmental contamination by pollutants detectable in the phytochemical profile and associations with stress biomarkers in the adaptive process of Laguncularia racemosa (L.) Gaertn (family Combretaceae), Avicennia germinans Stapf & Leechman and Rhizophora mangle L. (family Rhizophoraceae) and identified the biochemical, morphological and anatomical responses of these species in the Itaqui port area. The study areas were Porto do Itaqui (area considered impacted), located in the municipality of São Luís/MA (latitude 02°34'S - 02°36'S and 44°21'W - 44°24W) and the control area: Mangue Seco, municipality of Raposa, MA, (2o27'06.86” and 2o27'21.81” S and 44o09'20.33” and 44o09'45.76”W). The sample collection points were georeferenced with the aid of Garmim GPS. The sediment from the control area indicated a predominance of coarse, poorly selected silt, while analyzes of the Porto sediment sample showed 76.31% of medium silt, indicating muddy, poorly selected sediment. The organic matter content in the sediment was higher in Porto (10.78%) than in the control points (1.5% and 2.8%). Water analyzes showed significant differences in TSS, M.O, Turbidity and O.D. The phytochemical profile revealed significant changes in the port and control species. In samples from the port, the presence of medium polarity substances was observed in R. mangle. The green leaves of A. germinas showed a higher concentration of polar compounds, as in L. racemosa. In this case, the senescent leaves showed greater differences in terms of the amount of polar compounds and the production of tannins was not seen. Chlorophyll content a, b and total showed that the mangrove in the port area is significantly eutrophicated in relation to the control mangrove and high levels of chlorophyll in the leaves can be used as an important indicator for polluted sites.